Le contrôle juridique des entreprises multinationales - Trotier, Benoît (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
The multinational enterprise (MNE) is clearly a major factor for economic development but it exacts a heavy toll upon nations : a genuine loss of economical and political autonomy. Both home and host countries may feel their national goals put in jeopardy due to centralized decisions and commercial practices of this type of firm. Thus, nations have conceived a wide variety of controls seeking to sway the behavior of the MNE but such controls tend to exacerbate tensions between home and host countries while compelling the MNE to work amidst contradictory regulations in an uncertain environment. On the international level, many agreements have been concluded or are being discussed within different organizations but none of them has resulted in a binding act with compelling effects on the MNE. Nonetheless, if these agreements are considered to be a pledge to pursue future multilateral action, they may be completed by an all-encompassing collection of industrial and financial data on MNE's as well as by bilateral conventions on the conditions of foreign investment.